PERAN MANAGERIAL KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN (Tinjauan dalam Perspektif Islam) - Eneng Sumarni (Program Studi Pendidikan Agama Islam, Universitas Majalengka, 2023)
Quality education in each school is determined by very dominant factors including the strategic role of school principals in creating effective schools. schools in improving the quality of education is very significant with the role of the principal making efforts in accordance with the Managerial concept of the principal including: technical skills (technical skills), human relations skills (human relations skills), and skills conceptual (conceptual skills) rofessional school principals will be able to answer any problems that exist in education, because the more the times develop, the faster changes will occur in education